Underresearched tropical food crops: cowpea, banana and plantain, and yams - Asiedu, Robert; Fatokun, C.A.; Mignouna, J.H.; Ng, S.Y.C.; Quin, F.M.; Vuylsteke, D.R. (Springer, 1999)
For a mixture of reasons certain tropical crops which are important as primary or secondary food staples are relatively underresearched. The modem tools of molecular and cellular biotechnology offer the opportunity not only to make substantial gains in our knowledge of these crops, but also to overcome some of the obstacles which presently restrain both their genetic improvement and their productivity in tropical farming Systems. The crops considered here, cowpea (Vigna unguiculatd), banana and plantain (Musa spp.), and yams (Dioscorea spp.), typify this complex situation of importance combined with historical neglect.